Customers preferences of sense-based hotel’s guestroom attributes, experiences and satisfactions / Sharifah Norsabah Syed Abdullah - Syed Abdullah, Sharifah Norsabah (2013)
The purpose of this thesis is to determine the sense-based attributes that customers prefer in the five star hotel guestrooms. This study aims at contributing to the development of the knowledge regarding a sensory experience through quality management in the hotel industry. A quantitative approach has been used for this study, where theoretical concepts have been analyzed where the research objectives have been derived as means to test the study framework. In order to test the objectives, questionnaires has been self-administered outside the five star hotels in Kuala Lumpur city. The data gathered from the respondents was being analyzed through SPSS software. General pressumptions have then been drawn from the analysis of the results in order to provide sound recommendations for marketers regarding sensory experience in quality management program. The result of the study shows that it is beneficial for hoteliers to stage sense attributes based on sound, smell, touch and taste in the hotel guestrooms to enhance their satisfaction. The study shows that customers' prefer the sound, smell, touch and taste attributes to be presented in the guestrooms. The combination of the sense-base attributes contributes to an experience that is positive and memorable for the customers. Additionally, the results of this study shows that a combination of these sense-based attributes leads to satisfaction.